Implementação de modelo de otimização da política de reabastecimento para transportadores rodoviários de carga - Reduzino, Luciano Marques (2015)
The management of transportation is critical to the company's competitiveness as the cost of the road freight transport contributes to a large share of the total logistics cost. It is known transport in Brazil is highly concentrated by roads and one of the biggest costs of carriers is with the fuel (it is estimated that 17% of all logistics costs in existing carriers is spent on diesel). Analyzing the literature, it is possible to find some optimization models that take advantage of the difference in diesel prices between different gas stations to reduce spending by carriers with fuel. Within this context, it is also possible to select some patents on subjects close to the theme. Therefore this work aims to show the development of an accessible application to users through mobile devices that use these models and works as a decision support system to reduce the operating cost of transport undertakings of Brazilian road freight.